SIMULTANEOUS SEPARATION/PRECONCENTRATION OF NICKEL AND COBALT BY DISPERSIVE LIQUID-LIQUID MICROEXTRACTION PRIOR TO DETERMINATION BY FAAS - Rojas, F. Sanchez; Ojeda, C. Bosch; Pavon, J.M. Cano (European Scientific Journal, ESJ, 2013)
In this work, an efficient microextraction method was applied to the separation and preconcentration of Ni (II) and Co (II), namely dispersive liquid-liquid microextraction (DLLME). The influences of analytical parameters, including pH, extraction solvent volume, disperser solvent type and its volume, concentration of chelating agent, on the quantitative recoveries of nickel and cobalt were investigated. Under the optimized conditions, the detection limits were 1 μg L-1 and 3.5 μg L-1 for Ni and Co, respectively. The proposed method was applied to the determination of these elements in food samples with satisfactory results. The accuracy of the method was studied by analyzing certified reference materials.